Dimensi Manajemen Perubahan dalam Transformasi Pelayanan Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi (DPMPTSP) Aceh - Taufik, Taufik; Wardani, Suci Nanda; Amirulkamar, Said (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
Digital transformation in licensing services constitutes an integral part of bureaucratic reform that requires organizational adaptation grounded in change management principles. This study aims to analyze how the dimensions of awareness and ability influence organizational adaptation in the implementation of digital licensing services at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Aceh Province. The research employs a qualitative approach, with data collected through observation, in-depth interviews, and document analysis. Informants were selected purposively, and data were analyzed using the interactive model of Miles and Huberman. The findings indicate that, structurally, digital transformation has gained strong legitimacy through national regulations, which were internalized through official circular letters, coordination meetings, and internal communication forums. These strategies effectively fostered collective awareness among civil servants regarding the urgency of utilizing the Sicantik Cloud application. The ability dimension was strengthened through training programs and technical assistance, enhancing employees’ competencies in operating the online service system. However, external communication to the public remains reactive and limited, resulting in the continued dominance of face-to-face service preferences and suboptimal levels of independent online service utilization. The success of digital transformation is therefore determined not only by internal organizational readiness but also by effective public communication and community acceptance. The integration of awareness, ability, and proactive external communication strategies is essential to achieving effective, inclusive, and sustainable digital licensing services